Impact of Taraxerol in combination with extract of Euphorbia tirucalli plant on biological parameters of Lymnaea acuminata - Chauhan, Saroj; Singh, Ajay (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
The present work was carried out to evaluate the molluscicidal activity of active ingredient Taraxerol with the acetone extract of Euphorbia tirucalli against Lymnaea acuminata snail. The (fecundity, hatchability and survivability) of snail L. acuminata exposed to this extract was studied. The effects of the tested extracts on life-history traits of harmful snail L. acuminata have also been evaluated, and this study also expounds the inhibitory effects of these extracts singly as well as in binary combination (1:1 ratio). It concluded that these herbal products act as a potential source of molluscicides, and that they would also have the advantage of easy availability, low cost, biodegradability and greater acceptance amongst users than synthetic pesticide.